Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Answer:
x=2
Step-by-step explanation:
After solving with substitution, you would know x = 2
Step-by-step explanation:
[tex]\textsf{\large{\underline{Solution}:}}[/tex]
Given Equations:
→ 5x - 2y = 6 ----- (i)
→ 3x + 2y = 10 ---- (ii)
Adding (i) and (ii), we get:
→ 8x = 16
→ x = 16/8
→ x = 2
Substituting the value of x in (i), we get:
→ 5 × 2 - 2y = 6
→ -2y = 6 - 10
→ -2y = -4
→ y = -4/-2
→ y = 2
Therefore:
→ (x, y) = (2, 2) (Answer)
[tex]\textsf{\large{\underline{Verification}:}}[/tex]
Put x = 2 and y = 2 in second equation, the LHS becomes:
= 5 × 2 - 2 × 2
= 10 - 4
= 6
= RHS
Put x = 2 and y = 2 in second equation, the LHS becomes:
= 3 × 2 + 2 × 2
= 6 + 4
= 10
= RHS
Hence, our answer is correct (Verified)
Hope this helps!!
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.